Governance di Lingkungan Usaha Kecil Menengah Studi Empiris Pada Usaha Kecil Menengah di Propinsi DIY - Audita Nuvriasari; Uning Hadiyati (Universitas Islam Indonesia, 2008)
This study examines the implementation of good governance in Small Medium Sized Enterprises (SMEs). The specific purposes of this study are to analyzing: (1) the implementation of governance’s perspective: structure, mechanism, legal framework, regulations and business environment, (2) the perception of stakeholders (financial institutions) to the implementation of corporate governance in SMEs, (3) the differences of governance’s implementation in small business and medium business, (4) the differences of SMEs performance and (5) the relationship between corporate governance and firm performance.A sample of 60 SMEs and 10 financial institutions as stakeholders was used in this study. The tools that used in this study are: statistic descriptive, quartile, significant mean differences between two groups, regression and correlations. From this study can be concluded that the implementation of good corporate governance in SMEs are poor (score 0.3798 less than 0.50). Only 15% SMEs implementing corporate governance in good level and 85% in poor level. From statistic descriptive can be shown that the implementation of governance structure which consists of organizational structure and internal business process is weak to support the good corporate governance in SMEs. The governance mechanism which consists of corporate strategy, corporate policy and standard operating procedure can support the implementation of good corporate governance in SMEs. External forces including government regulation, business environment and legal framework is weak to support the implementation of good corporate governance in SMEs. From the comparison can be shown that there is no difference between the implementation of corporate governance in Small and Medium business. The business performance between Small and Medium business is different and there is a positive correlation between corporate governance and firm performance.Keywords: Small Medium Sized Enterprises, Good Corporate Governance, governance structure, governance mechanism, external forces